A Study on Perceptions, Practices, and Experiences About Antibiotic Consumption and Antibiotic Resistance Among Various Stakeholders From the Catchment Area of an Urban Health Training Centre in Ahmedabad - Nirmika Patel; Parita Patel; Rashmi Sharma; Brijesh Patel; Sanju Gajjar; Nirav Bapat (Healthline)
Introduction: Misuse or abuse of antibiotic consumption, leading to antibiotic resistance, is an emerging global public health issue. Therefore, this qualitative study was conducted with a primary objective of documenting the perceptions, practices and experiences about antibiotic consumption and awareness of antibiotic resistance among doctors, drug dispensers, and end-users. Objective: To document the perceptions, practices, and experiences about antibiotic consumption and awareness of antibiotic resistance amongst doctors, drug dispensers, and end-users. Method: A qualitative study was conducted in the UHTC catchment area, Ognaj, Ahmedabad. A total of 26 In-depth interviews with stakeholders (10 Doctors, 8 Drug dispensers and 8 End users) were conducted using an interview guide. Various themes and subthemes were categorized manually, and verbatim were quoted, at the end of all the In-depth interviews name of the antibiotics spoken was categories into Access, Watch and Reserve group as per WHO AWaRe classification and word cloud analysis was done. Results: Participated doctors had a wide range of qualifications and experience. It was found that doctors prescribe antibiotics mainly from the Access and Watch group (more from the Watch group). Drug dispensers were concerned about over-the-counter (OTC) dispensing and self-medication of antibiotics. However, they also shared the fact that the antibiotics are dispensed without prescriptions. End-users commonly sought antibiotics for minor ailments without prescriptions. Only one end user was aware of the implications of self-medication and resultant antibiotic resistance. Conclusion: Most antibiotics prescribed by doctors and dispensed at chemist shops were from the Watch and Access groups respectively. End users mainly purchased antibiotics from the Access and Watch groups. The findings highlight the urgent need for awareness sessions on antibiotic use and resistance for all stakeholders, along with stronger regulatory measures to control antibiotic sales by drug dispensers.